Dry reforming of methane over Ni-based catalysts: Effect of ZrO2 and MgO addition as support - Rosdin, R.D.B. (Elsevier B.V., 2021)
The increasing content of greenhouse gases (GHG's) in earth's atmosphere is the main reason for global warming. Dry reforming of methane (DRM) is an encouraging technique to utilize the two main GHG's (i.e., CO2 and CH4). Three different Ni based nano-catalysts i.e., Ni/Al2O3, Ni/Al2O3-ZrO2 and Ni/Al2O3-MgO were synthesized by wet-impregnation method and tested for DRM. The prepared catalysts were characterized via BET, XRD, FESEM-EDX, and TEM analysis, to determine the textural properties, phases, morphology, and elemental composition of catalysts. The catalysts were then tested for DRM at low reaction temperature of 650 Â°C. The Ni/Al2O3-MgO catalyst showed the optimum performance with elevated conversions of CH4 and CO2, followed by Ni/Al2O3 and Ni/Al2O3-ZrO2 catalysts, respectively. Â© 2021 The Author(s)